2009
DOI: 10.1128/aem.00383-09
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Saccharomyces cerevisiae for Production of Novel Cyanophycins with an Extended Range of Constituent Amino Acids

Abstract: Cyanophycin (multi-L-arginyl-poly-L-aspartic acid; also known as cyanophycin grana peptide [CGP]) is a putative precursor for numerous biodegradable technically used chemicals. Therefore, the biosynthesis and production of the polymer in recombinant organisms is of special interest. The synthesis of cyanophycin derivatives consisting of a wider range of constituents would broaden the applications of this polymer. We applied recombinant Saccharomyces cerevisiae strains defective in arginine metabolism and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
47
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 50 publications
4
47
1
Order By: Relevance
“…The major part accounts for a water-soluble form, and a minor part accounts for an insoluble form. Metabolic engineering of S. cerevisiae confirmed the results of Krehenbrink et al (6) concerning the incorporation of lysine (16 mol%), citrulline (20 mol%), and ornithine (8 mol%) in CGP synthesized by CphA 6308 (13). Wiefel et al (14) also demonstrated that in recombinant P. putida ATCC 4359 expressing cphA 6308 , a soluble polymer could be isolated consisting of 8 mol% lysine and 8 mol% citrulline instead of arginine.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…The major part accounts for a water-soluble form, and a minor part accounts for an insoluble form. Metabolic engineering of S. cerevisiae confirmed the results of Krehenbrink et al (6) concerning the incorporation of lysine (16 mol%), citrulline (20 mol%), and ornithine (8 mol%) in CGP synthesized by CphA 6308 (13). Wiefel et al (14) also demonstrated that in recombinant P. putida ATCC 4359 expressing cphA 6308 , a soluble polymer could be isolated consisting of 8 mol% lysine and 8 mol% citrulline instead of arginine.…”
supporting
confidence: 58%
“…Amino acid constituents of isolated CGP were determined by high-performance liquid chromatography (HPLC) with a Waters B801 column (300 by 4 mm) as described by Aboulmagd et al (25) and Steinle et al (13). Precolumn o-phthalaldehyde derivatization was carried out in a Smartline Autosampler 3900 (Knauer GmbH, Berlin, Germany) as described in the manual.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid constituents of isolated CGP and CGP dipeptides were determined by high-performance liquid chromatography (HPLC) using a Waters B801 (300-by 4-mm) column as described by Aboulmagd et al (17) and Steinle et al (7). Precolumn OPA derivatization was done with a Smartline autosampler 3900 as described in the manual (Knauer GmbH, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…CGP is interesting due to its easy and lowcost purification using alternating steps of solubilization in 0.1 M HCl and precipitation by neutralization to pH 7 (5). Also of interest is the possibility of obtaining CGP with different side chains in which L-arginine is replaced by other compounds, like lysine (6), ornithine (7), or citrulline (7,8). Synthesis of these forms of CGP became possible because the amino acids mentioned also possess a certain affinity for the cyanophycin synthetase CphA (EC 6.3.2.29 and EC 6.3.2.30).…”
mentioning
confidence: 99%
See 1 more Smart Citation